THE OCCURANCE OF DEIXIS USING “WRECK-IT RALPH” MOVIE SCRIPT - Zhafirah Nurul Idzni; Nai Supartini Atmawidjaja (PROJECT (Professional Journal of English Education), 2022)
This study deals with the English deixis. The objectives of this study are to analyze type of deixis and to find out frequency of each deixis in the movie entitled Wreck-It Ralph. This study was conducted by using descriptive qualitative research. The source of data was taken from the movie script of Wreck-It Ralph. Documentary technique is used in collecting data. The findings showed that there are three types of deixis found in the Wreck-It Ralph movie script and there are nine frequencies of deixis, namely person deixis in greater occurrences than another. Type of person deixis is used 336 times or (94, 37%), which contains of first person used 237 times or (66,57%), second person used 56 times or (15,73%), and third person used 43 times or (12,07%). The next, spatial (place) deixis is used 16 times or (4,49%) and the last, temporal (time) deixis is used 4 times or (1,12%) which consist of present used 2 times or (0,56%), past used 1 time or (0,28%), future used 1 time or (0,28%). Keywords:  Pragmatic, Movie, Deixis